"He Can't Say a Man's Stuff to a Woman…": Perspectives on the Preferences of Men Living with HIV for Gender-Concordant Care Workers in Cape Town, South Africa. (December 2019) - Gittings, Lesley
Community health workers (CHWs) play a central role in the provision of HIV care in South Africa, and people receiving such community-based adherence support have considerably better health outcomes. As with other forms of care work, the majority of CHWs are women. HIV vulnerability is also gendered, with women being more likely to contract HIV, while men living with HIV are more likely to die of AIDS-related illness. This article explores the relational gender dynamics of eight Cape Town–based CHWs and their male clients. Derived from multiple semistructured interviews, it engages the perspectives of CHWs, men living with HIV, and HIV and masculinities activists to explore HIV-positive men's gender preferences for CHWs, and how these pairings may support their health and well-being. Reasons cited for gender-concordant preferences include gendered power dynamics, comfort in sharing intimate health information of someone of the same gender, and, in some cases, negative associations of women as untrustworthy gossips.